Development of a speech analyser/synthesizer for special applications in linguistics - Sivaprakasapillai, Pratab (2008)
This project on the development of a speech analyzer/synthesiser for special applications in linguistics was proposed for the purpose of developing computer software for the alteration of the prosodic characteristics of speech signals in the English Language.